Non-specific labeling limits the utility of Cre-Lox bred CST-YFP mice for studies of corticospinal tract regeneration - Willenberg, Rafer (J Comp Neurol, 2015)
Studies of axon regeneration in the spinal cord often assess regeneration of the corticospinal tract (CST). Emx1-Cre x Thy1-STOP-YFP mice have been reported to have yellow fluorescent protein (YFP) selectively expressed in forebrain neurons leading to genetic labeling of CST axons in the spinal cord, and it was suggested that these CST-YFP mice would be useful for studies of CST regeneration. Because regeneration past a lesion may involve only a few axons, the presence of labeled non-CST axons compromises interpretation. We show here that in CST-YFP mice, some YFP-labeled axons are not from the CST. Specifically, YFP-labeled axons are present in regions beyond those with anterogradely-labeled CST axons, most YFP-labeled axons beyond established CST locations do not undergo Wallerian degeneration following a large lesion of the sensorimotor cortex, some rubrospinal and reticulospinal neurons are labeled with YFP, and some YFP-labeled cells in the spinal grey matter have YFP-labeled projections into the spinal cord white matter. We further demonstrate that the density of YFP-labeled axon arbors hinders tracing of single axons to their point of origin in the main descending tracts. In light of recent advances in 3D imaging for visualizing axons in un-sectioned blocks of spinal cord, we also assessed CST-YFP mice for 3D imaging and found that YFP fluorescence in CST-YFP mice is faint for clearing-based 3D imaging in comparison to fluorescence in Thy1-YFP-H mice and fluorescence of mini-ruby BDA. Overall, the non-specific and faint YFP labeling in CST-YFP mice limit their utility for assessments of CST axon regeneration.